A novel helmet-mounted device for reducing the potential of catastrophic cervical spine fractures and spinal cord injuries in head-first impacts. (April 2019) - Dressler, Daniel M.; Dennison, Christopher R.; Whyte, Tom; Cripton, Peter A.
Abstract: Background: Head-first impacts with an aligned cervical spine cause some of the most severe types of injuries due to the risk of fractures and associated spinal cord injury. Sports, such as football, mountain biking and horseback riding, contribute to the incidence of spinal cord injury but there is potential to reduce the risk of these injuries through a helmet-mounted device. Methods: A novel device, the Pro-Neck-Tor mechanism, was incorporated into a commercial football helmet and tested in head-first impact experiments. The Pro-Neck-Tor connects an inner and outer helmet shell, which upon head-first impact of a certain load, induces motion of the head away from the path of the following torso. Impacts were performed onto three impact surface angles with a flexion-inducing Pro-Neck-Tor mechanism. Findings: Based on averaged data, the Pro-Neck-Tor provided a significant and consistent reduction in peak compressive neck forces compared to the unmodified football helmet in the conditions tested. In some impact conditions, the Pro-Neck-Tor increased the peak sagittal plane neck bending moments and impulse over that observed for the unmodified helmet. Interpretation: The Pro-Neck-Tor with flexion escape is capable of lowering axial neck forces in head-first impacts compared to a conventional helmet by guiding the cervical column away from an aligned posture and into an eccentric loading scenario which published studies suggests frequently leads to no injury or to a less severe injury. Continued development and testing of the device are needed to optimize the altered neck loading and to drive the design toward a commercial configuration. Highlights: The Pro-Neck-Tor device alters the head and neck loading in head-first impacts. Compressive neck forces were consistently reduced due to the Pro-Neck-Tor. Neck bending moments were increased due to the Pro-Neck-Tor in some circumstances. Such loading changes may reduce the potential for catastrophic cervical injury.